Clinical efficacy of percutaneous closure of patent foramen ovale in children diagnosed with migraine - Yakun Wang; Xingmiao Liu; Ji Cheng; Dong Li (Frontiers in Cardiovascular Medicine)
ObjectiveThis retrospective analysis aimed to assess the clinical efficacy of patent foramen ovale (PFO) closure for the treatment of migraine in children.MethodsData from 35 children diagnosed with migraine and PFO (pre-intervention transthoracic echocardiography did not detect PFO in some, but saline contrast echocardiography was positive, indicating hidden PFO), admitted to Tianjin Children's Hospital for PFO closure between March 2020 and February 2024, were retrospectively collected and analysed. The efficacy of post-intervention pain relief was evaluated using an 11-point numerical rating scale (NRS-11), headache impact test-6 (HIT-6), and Paediatric Migraine Disability Assessment Score (PedMIDAS), migraine frequency, and duration of each migraine attack.ResultsAt the 1-month follow-up after PFO closure, 20 patients (57.1%) achieved complete relief, and 29 (82.9%) had a reduction in migraine attack frequency by >50%. At the 12-month follow-up, 28 patients (80%) achieved complete relief, and 32 (91.4%) had a reduction in migraine attack frequency by >50%. There were no statistically significant differences between the aura and the non-aura groups. All patients exhibited statistically significant improvement (P < 0.05) in NRS-11, HIT-6, and PedMIDAS, migraine frequency, and duration of each migraine attack. The children in the aura group had a more significant decrease in NRS-11 than those in the non-aura group at 12-month after the operation (P < 0.05). Additionally, there were no statistically significant differences between the two groups in HIT-6, PedMIDAS, and duration of migraine attacks.ConclusionPercutaneous PFO closure demonstrated significant clinical efficacy and safety in the treatment of migraine in children.